A Review of Phenobarbital for Alcohol Withdrawal Syndrome - Saadatmand, Heva J.; Ho, Pochu (Current Psychopharmacology, 2021)
Background: Alcohol use disorder represents a serious health problem worldwide which is increasing in pervasiveness. Alcohol withdrawal syndrome is a common clinical problem encountered in emergency departments and inpatient settings, including intensive care units. While benzodiazepines are the most widely used class of medication for the treatment of alcohol withdrawal, in recent years, there is renewed interest in using phenobarbital, a barbiturate, in the treatment of refractory alcohol withdrawal. Objective: This review provides an overview of phenobarbital in the treatment of alcohol withdrawal, as well as clinical outcomes in patients, while also outlining some of the limitations of existing studies in comparing phenobarbital to benzodiazepines. Methods: PubMed, Ovid MEDLINE, and Cochrane databases were searched using the terms phenobarbital, barbiturates, and alcohol withdrawal syndrome. Prospective and retrospective trials comparing phenobarbital with benzodiazepines to treat alcohol withdrawal in English were included. Results: Two prospective randomized controlled and eleven retrospective cohort trials were identified. Phenobarbital is safe alone and as an adjunct to benzodiazepine in the emergency department, intensive care units, general medical units and acute trauma surgery service. In a randomized controlled trial, one dose of phenobarbital in the emergency department significantly reduced the intensive care admission rate. There is some evidence that phenobarbital may be effective in the treatment of benzodiazepine- refractory alcohol withdrawal. Conclusion: Although existing knowledge and practice regarding phenobarbital for the treatment of alcohol withdrawal are increasing, there currently remains limited evidence in support of phenobarbital over benzodiazepines in superior efficacy and outcomes.
Keywords: phenobarbital